Azure platform as a service : web and API application deployment (Packt Publishing, 2018)
"Microsoft Azure provides various services to enable Platform as a Service-based cloud development, allowing you to deliver both simple cloud-based applications and sophisticated and heavy-duty cloud-based enterprise services. This video tutorial will provide you with the necessary know-how to leverage Azure services to build your own PaaS cloud. You'll start by exploring Azure App Services, and learn to work with supported application types based on different parameters such as languages and functions. You'll learn to configure, publish, secure, and analyze your application APIs with Azure API management. Going further, you will learn to leverage Database as a Service in Azure, and work with different options for database management and also different types of databases such as MySQL and PostgreSQL. You'll even learn to develop NoSQL databases with the help of Azure Table Storage. Next, you will delve into Data Processing as a Service, and learn how to create custom searches for your application, enable messaging between applications and services, and work with data using Azure Data Factory and Azure Data Catalog."--Resource description page